The utility of methylmalonic acid, methylcitrate acid, and homocysteine in dried blood spots for therapeutic monitoring of three inherited metabolic diseases - Liu, Yi; Ma, Xue; Kang, Lulu; Jin, Ying; Li, Mengqiu; Song, Jinqing; Li, Haixia; Cao, Yongtong; Yang, Yanling (Frontiers in Nutrition, 2024)
Backgroud: Routine metabolic assessments for methylmalonic acidemia (MMA), propionic acidemia (PA), and homocysteinemia involve detecting metabolites in dried blood spots (DBS) and analyzing specific biomarkers in serum and urine. This study aimed to establish a liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for the simultaneous detection of three specific biomarkers (methylmalonic acid, methylcitric acid, and homocysteine) in DBS, as well as to appraise the applicability of these three DBS metabolites in monitoring patients with MMA, PA, and homocysteinemia during follow-up.Methods: A total of 140 healthy controls and 228 participants were enrolled, including 205 patients with MMA, 17 patients with PA, and 6 patients with homocysteinemia. Clinical data and DBS samples were collected during follow-up visits.The reference ranges (25th -95th percentile) for DBS methylmalonic acid, methylcitric acid, and homocysteine were estimated as 0.04-1.02 μmol/L, 0.02-0.27 μmol/L and 1.05-8.22 μmol/L, respectively. Following treatment, some patients achieved normal metabolite concentrations, but the majority still exhibited characteristic biochemical patterns. The concentrations of methylmalonic acid, methylcitric acid, and homocysteine in DBS showed positive correlations with urine methylmalonic acid (r = 0.849, P < 0.001), urine methylcitric acid (r = 0.693, P < 0.001), and serum homocysteine (r = 0.721, P < 0.001) concentrations, respectively. Additionally, higher levels of DBS methylmalonic acid and methylcitric acid may be associated with increased cumulative complication scores.The LC-MS/MS method established in this study reliably detects methylmalonic acid, methylcitric acid, and homocysteine in DBS. These three DBS metabolites can be valuable for monitoring patients with MMA, PA, and homocysteinemia during follow-up. Further investigation is required to determine the significance of these DBS biomarkers in assessing disease burden over time.